Contributions and future priorities for soil science: comparing perspectives from scientists and stakeholders - Cimpoiasu, Mihai O.; Dowdeswell-Downey, Emily; Evans, Daniel L.; McCloskey, Christopher S.; Rose, Lewis S.; Sayer, Emma J. (Wiley, 2021)
Soils are a fundamental natural resource but intensifying demands and increasing soil degradation necessitate focussed research into the sustainable use of soils. Since soil functioning is critical for the operations and performance of multiple industries, businesses and municipalities, soil scientists need to actively engage with these bodies to orientate research goals towards stakeholder needs. To achieve this, stakeholder views about the current and potential contributions of soil science to different sectors need to be taken into account when setting the future research agenda. Here, we assessed whether the current and future research priorities of soil science match the needs of four major industrial and environmental sectors: agriculture, ecosystem services and natural resources, waste management, and water management. We used an online questionnaire, distributed to 192 organisations and via social media, to compare stakeholders' and scientists' perceptions of (a) the contributions of soil science to date, (b) the areas not currently served by soil science and (c) future research needs in soil science. Stakeholders generally rated the contributions of soil science to date as ‘great’ or ‘fundamental’, but scientists rated the contributions more highly. Respondents identified numerous areas that soil research has not yet sufficiently addressed, which were mostly sector-specific and often overlapped with perceived future research needs. Importantly, stakeholders' and scientists' views of future research priorities differed strongly within sectors, with the notable exception of agriculture, where views were generally consistent. We conclude that soil science may hold unexplored potential in several industrial and environmental sectors. We call for improved research communication and greater stakeholder involvement to shape the future soils research agenda and ensure the sustainable use of soils across multiple areas of society.
Keywords: Soil research priorities; soil research status-quo; survey-based study; agriculture; ecosystem services; waste management; water management; industry-focused research; research gaps